Time for a Systems Biological Approach to Cognitive Aging?—A Critical Review - Ebaid, Deena; Crewther, Sheila G. (Frontiers in Aging Neuroscience, 2020)
The underlying premise of current theories of cognitive decline with age, tend to be primarily cognitive or biological explanations, with relatively few theories adequately integrating both aspects. Though cognitive aging literature has also emphasised the importance of several factors that contribute to cognitive aging including a) decline in sensory abilities, b) the effect of motor speed on paper-pencil task measures of cognitive speed, c) the impact of level of education and physical activity on cognitive aging, and d) molecular biological changes that occur with age, these factors have seldom been implicated into any single theoretical model of cognitive aging. Indeed, such an integrated bio-cognitive model of aging has potential to provide a more comprehensive understanding of attention, perception, learning and memory across the lifespan. Thus, the aim of this review was to critically evaluate common theories of age-related cognitive decline and highlight the need for a more comprehensive systems neuroscience approach to cognitive aging.